Effect of metal-based nanoparticles decorated graphene hybrids on flammability of epoxy nanocomposites. (February 2020) - Kalali, Ehsan Naderi; Guo, Wenwen; Wang, Xin; Xing, Weiyi; Song, Lei; Hu, Yuan
Abstract: To overcome the flammability of epoxy resins (EPs), metal-based nanoparticles decorated reduced graphene oxide (rGO) hybrids including Ag@rGO, Cu2 O@rGO and TiO2 @rGO, were synthesized through microwave irradiation technique and subsequently incorporated into EPs. The structure and morphology of the metal-based nanoparticles decorated rGO hybrids were characterized by XRD, XPS, TEM and SEM, which confirmed successful synthesis of the hybrid materials. The metal-based nanoparticles were uniformly deposited to the rGO nanosheets, which could avoid re-stacking of graphene nanosheets. The addition of metal-based nanoparticles decorated rGO hybrids significantly diminished the flammability of epoxy nanocomposites. Specifically, the Cu2 O@rGO/EP nanocomposite showed 50% and 29% reduction in peak heat release rate and total smoke production, respectively. The reduced flammability was attributed to the improved char yield that restrained the heat and smoke release during combustion. It is prognosticated that metal-based nanoparticles decorated graphene hybrids will provide an efficient solution to improve fire safety of polymeric materials.